Implementasi Budaya Sekolah Islami dalam Pembentukan Karakter Religius Siswa SMK Islam Insan Mulia - Nauroh Nurhumaida; Sinta Nuraini; Dhea Andaresta (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
This study aims to describe the implementation of Islamic school culture in shaping the religious character of students at SMK Islam Insan Mulia. The research employed a descriptive qualitative approach based on interview transcripts with three students from different vocational programs, namely Mechanical Engineering, Accounting, and Culinary Arts. Data were analyzed through data condensation, thematic coding, data presentation, and interpretive conclusion drawing to obtain a comprehensive understanding of students’ experiences. The findings indicate that Islamic school culture is implemented through religious routines, student discipline, teacher guidance, ethical vocational learning, and the development of a clean and orderly school environment. These practices contribute to the formation of religious character, which is reflected in students’ worship awareness, moral responsibility, honesty in learning, discipline, cooperation, and future orientation. The study also identified several challenges, including limited student independence, peer dependence in group assignments, and the gradual development of facilities in a new vocational program. These findings suggest that Islamic school culture needs to be managed consistently through habituation, teacher role modeling, continuous monitoring, and integration with vocational competencies. The study implies that strengthening Islamic school culture can support both religious character formation and vocational readiness among students.